Fenomena Stigma Maskulinity Terhadap Fanboy Kpop di Kota Medan - Ummi, Rizka Fadhilatil; Zahra, Sylva; Sazali, Hasan (Institut Agama Islam Nasional Laa Roiba Bogor, 2023)
Changes in the meaning of men which are symbolized by k-pop boy bands foster a new ideology of maleness or masculinity. This ideology opens up a new social space for placing adolescents with their male identity built on aspects constructed by k-pop boy bands. This identity then becomes an interesting discourse to examine, with the question of how the meaning of masculinity is constructed, consumed and deconstructed by K-Pop fans. The researcher uses a qualitative approach with the aim of uncovering the data described by data sources and participants to find out about how the technological aspects of the library cooperation network and digital library information in the city of Medan, to obtain quality results from the research conducted. The results of this study resulted in the phenomenon of K-Pop boygroup fanboy masculinity which can create a stigma of masculinity that is given and even labeled for men who like K-Pop or become fanboys of K-Pop boygroups. There are already many non-K-Pop people or men who are literate and aware of the meaning of male masculinity, which does not have to be defined by having a well-built body, tanned and black skin, having a firm face and jawline that reflects a strong male figure. .. Keywords: Gender, Kpop, Masculinity